2012
DOI: 10.1038/cr.2012.176
|View full text |Cite
|
Sign up to set email alerts
|

Piglets cloned from induced pluripotent stem cells

Abstract: Figure 1Derivation and characterization of cloned piglets from piPSCs. (A) Preimplantation and post-implantation development of the cloned embryos from piPSCs. Embryos at two-cell (a), four-cell (b), eight-cell (c), blastocyst stages (d, e) and two 36 day-old cloned fetuses (f) are shown. Scale bars are 100 μm. (B) The morphology and fluorescence of the hooves (left), tails (middle) and fibroblasts (right) of the 36 day-old embryos. Scale bars are 100 μm. (C) The morphology, fluorescence and hematoxylin/eosin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 11 publications
6
92
0
Order By: Relevance
“…Recently, several groups described the derivation of porcine induced pluripotent cells (iPS) [16][17][18][19][20] , however, only low chimerism has been found after blastocyst complementation experiments 21,22 . The employment of porcine iPS cells in the SCNT method resulted in extremely low rates of born piglets 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups described the derivation of porcine induced pluripotent cells (iPS) [16][17][18][19][20] , however, only low chimerism has been found after blastocyst complementation experiments 21,22 . The employment of porcine iPS cells in the SCNT method resulted in extremely low rates of born piglets 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, to correct or relieve the incomplete epigenetic reprogramming of cloned embryos, different cell types were used as the nuclear donor for pig SCNT, such as fetal fibroblasts (FFs; Onishi et al, 2000), preadipocytes (Tomii et al, 2005), adult mesenchymal stem cells (MSCs; Faast et al, 2006), recloned pig somatic cells (Cho et al, 2007), and induced pluripotent stem cells (iPSCs; Fan et al, 2013).…”
mentioning
confidence: 99%
“…High proliferation activity of pPiPSCs and their differentiated cells may satisfy the long-term requirement of in vitro cellular drug screening, although further studies are required to confirm this. During SCNT from iPSCs, insufficient silencing of exogenous genes would compromise the development of reconstructive embryos (Fan et al 2013). Thus, differentiated cells from pPiPSCs and pFiPSCs were used for SCNT.…”
Section: Discussionmentioning
confidence: 99%
“…West et al (2011) established chimeric pigs from mesenchymal stem cell (MSC)-derived iPSCs, and, although this was controversial, it has been suggested that MSC-derived iPSCs may be beneficial for the generation of porcine offspring. Fan et al (2013) studied iPSCs and differentiated porcine iPSCs, and concluded that the expressions of exogenous transcription factors in porcine iPSCs have a negative effect on the production of iPSC-derived clone pigs. Accordingly, we wonder whether pADSC-derived PiPSCs with the perfect regulation exogenous gene expression are beneficial for the development of SCNT embryos.…”
Section: Introductionmentioning
confidence: 99%